Towards the holy grail of cross-border payments - Ulrich Bindseil; George Pantelopoulos (European Central Bank (ECB), 2022)
The holy grail of cross-border payments is a solution allowing cross-border payments to be immediate, cheap, universal, and settled in a secure settlement medium. The search for such a solution is as old as international commerce and the implied need to pay. This paper describes current visions how to eventually find this holy grail within the next decade, namely through (i) modernized correspondent banking; (ii) emerging cross-border FinTech solutions; (iii) Bitcoin; (iv) global stablecoins; (v) interlinked instant payment systems with FX conversion layer; (vi) interlinked CBDC with FX conversion layer. For each, settlement mechanics are explained, and an assessment is provided on its potential to be the holy grail of cross-border payments. Several solutions are suitable for improving cross-border payments significantly, and some could even be the holy grail.
Keywords: E42; E58; F31; 330; cross-currency payments; bitcoin; correspondent banking; stablecoins; interlinking; CBDC